2018
DOI: 10.1007/s11695-017-3102-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vitamin B12 Supplementation After Roux-en-Y Gastric Bypass: a Systematic Review

Abstract: The review finds that oral supplementation doses of ≤ 15 μg vitamin B daily are inadequate for prophylaxis of vitamin B deficiency in adult RYGB patients but doses of 1000 μg vitamin B daily might be adequate. Future studies need to examine this and even higher oral doses for vitamin B supplementation for patients undergoing RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Vitamin B12 absorption is adversely affected by SG, RYGB and BPD/DS as it requires an acidic environment and presence of intrinsic factor produced by the gastric parietal cells 95 . Many people have about 2‐year stores of vitamin B12; therefore, deficiency may present several years after surgery 15,18,19,40,41,47,57–59,65,73,86–89,92,93,96 . Vitamin B12 deficiency impacts adversely on the haematopoietic and nervous systems and may result in megaloblastic anaemia and irreversible neuropathies 95 .…”
Section: Postoperative Care and Biochemical Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B12 absorption is adversely affected by SG, RYGB and BPD/DS as it requires an acidic environment and presence of intrinsic factor produced by the gastric parietal cells 95 . Many people have about 2‐year stores of vitamin B12; therefore, deficiency may present several years after surgery 15,18,19,40,41,47,57–59,65,73,86–89,92,93,96 . Vitamin B12 deficiency impacts adversely on the haematopoietic and nervous systems and may result in megaloblastic anaemia and irreversible neuropathies 95 .…”
Section: Postoperative Care and Biochemical Monitoringmentioning
confidence: 99%
“…Further research is needed, as deficiency may still occur in the presence of high oral doses 34,92,136 . Adherence to oral supplementation is more difficult to determine 34,96,133–135 . Given the serious consequences of vitamin B12 deficiency, we recommend routine supplementation with three monthly intramuscular vitamin B12 injections for SG, RYGB and malabsorptive procedures such as BPD/DS 134 …”
Section: Vitamin and Mineral Supplementationmentioning
confidence: 99%
“…The multivitamin used in the study by Homan et al included 350 μg of vitamin B 12 [48], which may be sufficient to overcome deficiency as 1-5% of vitamin B 12 is absorbed by an intrinsic factor-independent mechanism [16]. However, other studies demonstrated higher doses of oral hydroxocobalamin are required, with 1000 μg per day proving optimal to manage vitamin B 12 deficiency after GB [50]. Furthermore, in a study comparing oral and intramuscular cobalamin, there was no significant difference in improvement in vitamin B 12 levels, suggesting that high-dose oral vitamin B 12 (1000 μg per day) is sufficient to overcome deficiency [51].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate dosages for various micronutrient supplementations after RYGB are now becoming clearer [47][48][49][50][51] but there is as yet no clarity on these doses for patients undergoing OAGB even though there is consensus [3] that these patients need lifelong supplementation with iron, vitamin D and Calcium, Vitamin B12, and a multivitamin containing appropriate amounts of Zinc and Copper.…”
Section: Prevention and Management Of Micronutrient Deficiencymentioning
confidence: 99%
“…We hypothesise that OAGB patients should be advised lifelong supplementation with a) two multivitamin/mineral tablet, each containing at least 1.0 gram of Copper and 15 mg of Zinc b) parenteral supplementation with 1 mg vitamin B12 every 3 months or oral supplementation with 1.5 mg vitamin B12 daily c) Iron supplementation with at least 120 mg elemental iron daily d) Calcium supplementation with 1500 mg elemental calcium, and e) vitamin D 3000 international units daily. These doses are based on our experience with OAGB [46] and the literature on RYGB extrapolated to higher requirements with OAGB [47][48][49][50][51]. We believe these dosages can serve as useful starting points for the supplementation of various micronutrients after OAGB until further data emerges.…”
Section: Prevention and Management Of Micronutrient Deficiencymentioning
confidence: 99%